The Block Matching Algorithm and Its Use for Vehicle Motion Description - Martin Capka (Communications - Scientific letters of the University of Zilina, 2005)
This paper deals with principles of Block Matching Algorithm (BMA) and its use for vehicle detection and tracking. The Block matching plays essential role in motion estimation employed in the MPEG compression standard. The current frame is divided by BMA in smaller, fixed size blocks. These blocks are then matched in the previous frame in order to estimate their displacement between two successive frames. BMA supplies us with information referred to as motion vectors. Motion vectors are next processed to gain relevant data for vehicle detection and tracking.